666 Complete vs. culprit-only strategy in older MI patients with multi-vessel disease. (8th December 2021) - Caglioni, Serena; Mele, Daniela; Verardi, Filippo Maria; Campana, Roberta; Erriquez, Andrea; Pompei, Graziella; Biscaglia, Simone
Abstract: Aims: The revascularization strategy to pursue in older myocardial infarction (MI) patients with multivessel disease (MVD) is currently unknown. For this reason, while waiting for the results of dedicated trials, we sought to compare a complete vs. a culprit-only strategy in older MI patients by merging data from four registries. Methods and results: The inclusion criteria for the target population of the present study were: (i) age ≥75 years; (ii) MI (STE or NSTE); (iii) MVD; and (iv) successful treatment of culprit lesion. Propensity scores (PS) were derived using logistic regression (backwards stepwise selection, P < 0.2. The primary outcome was all-cause mortality. Secondary outcomes were cardiovascular (CV) death, MI, major bleeding. Multivariable adjustment included the PS and inverse probability of treatment weighting (IPTW). The Kaplan–Meier plots were weighted for IPT. Among 2087 patients included, 1362 (65%) received culprit-only treatment whereas 725 (35%) complete revascularization. The mean age was 81.5 years, while mean Follow-up was 419 ± 284 days. Seventy-four patients (10%) died in the complete group and 223 in the culprit-only one (16%). The adjusted cumulative 1-year mortality was 9.7% in the complete and 12.9% in the culprit-only group (adjusted HR: 0.67, 95% CI: 0.50–0.89). Complete revascularization was associated with lower incidence of CV death (adjusted HR: 0.68, 95% CI: 0.48–0.95) and MI (adjusted HR: 0.67, 95% CI: 0.48–0.95). Conclusions: Culprit-only is the default strategy in older MI patients with MVD. In our analysis, complete revascularization was associated with lower all-cause and CV mortality and with a lower MI rate.